Responsible Production and Consumption in a Local Environment: Municipality, Citizenship and Recycling Industry. - Ramos Martínez, Priscila Nayeli; Martínez Jiménez, Rosa María; Hernández Triano, Leonardo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To know the relationship between local governments, citizens and organizations dedicated to recycling with responsible production and consumption, and its effects on sustainable development.MATERIALS AND METHOD: The research is qualitative, supported by the techniques: in situ observation, carried out on collection routes, and interviews, applied to collection service workers in the municipality of Centro, Tabasco.RESULTS: The contribution of Urban Solid Waste [USW] of the State of Tabasco is 2.3 tons per day, derived from a population of 2,402,598 that generates .98 kg. of waste daily. The municipality of Centro, Tabasco has a population of 683,607 inhabitants, who contribute with an average of 663 tons of USW per day, reaching an approximate of 19,893 tons per month.CONCLUSIONS: The increase in USW is related to urban growth, industrial development, technological modifications, and changes in the population's consumption patterns; the higher the income, the higher the consumption. Mexico leads the generation of USW in Latin America, with an estimated average of 46 million tons by 2022, so there is a proportional relationship between income and consumption with waste generation.
Keywords: Responsible consumption; Business environment; USW management.